2018
DOI: 10.2147/jpr.s160659
|View full text |Cite
|
Sign up to set email alerts
|

Oxycodone ameliorates the inflammatory response induced by lipopolysaccharide in primary microglia

Abstract: BackgroundActivation of microglia participates in a wide range of pathophysiological processes in the central nervous system. Some studies reported that oxycodone (6-deoxy-7,8-dehydro-14-hydroxy-3-O-methyl-6oxomorphine) could inhibit the overactivation of glial cells in rats’ spinal cords. In the present study, we observed the effect of oxycodone on inflammatory molecules and pathway in lipopolysaccharide (LPS)-stimulated primary microglia in rats.Materials and methodsNeonatal rats’ primary microglia were expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Oxycodone is a widely used analgesic due to its several advantages. Except for μ and κ receptor activation, the attenuation of the inflammatory response in microglia and the regulation of GABAB receptor are also involved in the analgesic effect of oxycodone, especially for chemotherapy-induced neuropathic pain [23, 24]. In our study, we demonstrated that oxycodone can inhibit the inflammation in the primary microglia induced by vincristine, which may be related to the reduction of CXCL10 and CXCL9 expression.…”
Section: Discussionmentioning
confidence: 53%
“…Oxycodone is a widely used analgesic due to its several advantages. Except for μ and κ receptor activation, the attenuation of the inflammatory response in microglia and the regulation of GABAB receptor are also involved in the analgesic effect of oxycodone, especially for chemotherapy-induced neuropathic pain [23, 24]. In our study, we demonstrated that oxycodone can inhibit the inflammation in the primary microglia induced by vincristine, which may be related to the reduction of CXCL10 and CXCL9 expression.…”
Section: Discussionmentioning
confidence: 53%
“…Walentiny et.al found that nociceptin/orphanin FQ (NOP) receptor activation can modulate the discriminative stimulus effects of oxycodone in C57BL/6 mice [12]. In vivo and vitro, some results of researches also demonstrated that oxycodone could decrease spinal nerve injury (SNL)-induced activation of glial cells (astrocytes and microglia) and plasma levels of proinflammatory cytokines (IL-6, IL-1β and TNF-α) [13, 14]. In consideration of opioids-drugs abuse, Zhang et al found several alterations of expression of genes related to inflammation/immune functions in the dorsal striatum of adult C57BL/6J mice following chronic oxycodone self-administration, which revealed some novel neurobiological underlying mechanisms of abused prescription opioid [15].…”
Section: Discussionmentioning
confidence: 99%
“…These unexpected findings suggest that treatment with Oxy may increases risk of cognitive complications. Several studies suggested that Oxy can relieve the inflammatory response [12,13], so we hypothesized that Oxy could reduce inflammatory reaction and improve postoperative cognitive function. However, our study data contradict this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Oxycodone (Oxy), a μ and κ opioid receptor agonist, is increasingly used worldwide to treat a variety of painful disorders [11]. Recently, several studies suggested that Oxy not only provides potent analgesia but also relieves the inflammatory response [12,13]. To date, no study has investigated the anti-inflammatory effects of Oxy in patients undergoing limb ischemia-reperfusion.…”
Section: Introductionmentioning
confidence: 99%